Simulation Sickness Evaluation While Using a Fully Autonomous Car in a Head Mounted Display Virtual Environment - Rangelova, Stanislava; Decker, Daniel; Eckel, Marc; Andre, Elisabeth (Virtual, Augmented and Mixed Reality: Interaction, Navigation, Visualization, Embodiment, and Simulation, 2018)
Simulation sickness is a condition of physiological discomfort felt during or after exposure to a virtual environment. A virtual environment can be accessed through a head mounted display which provides the user with an entrance to the virtual world. The onset of simulation sickness is a main disadvantage of virtual reality (VR) systems. The proof-of-concept presented in this paper aims to provide new insights into development and evaluation of a VR driving simulation based on consumer electronics devices and a 3 Degrees-of-Freedom (3 DOF) motion platform. A small sample (n = 9) driving simulator pre-study with within-subjects design was conducted to explore simulation sickness outbreak, sense of presence and physiological responses induced by autonomous driving in a dynamic and static driving simulation. The preliminary findings show that users experienced no substantial simulation sickness while using an autonomous car when the VR simulation included a motion platform. This study is the basis for more extensive research in the future. Future studies will include more participants and investigate more factors that contribute to or mitigate the effects of simulation sickness.